2011
DOI: 10.1111/j.1365-2745.2010.01784.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing predictions of a three‐species plant–soil feedback model

Abstract: Summary 1.A growing number of experiments measure plant growth on soils cultivated by different species. Models show that the resulting plant-soil feedbacks (PSFs) can determine plant abundance and persistence; yet, quantitative tests of their importance in community dynamics are lacking.2. Here, we use the growth of eight plant species on 'self' and 'other' soils to parameterize a threespecies PSF model. Predictions from the parameterized model were compared to plant growth observed in a 3-month glasshouse ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 36 publications
1
79
2
Order By: Relevance
“…However, in contrast to previous continuous-time models [14,[16][17][18], we use a discrete-time approach that provides specific estimates of plant and soiltype biomass (e.g. A and SA; table 1) and is easily implemented in a spreadsheet.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, in contrast to previous continuous-time models [14,[16][17][18], we use a discrete-time approach that provides specific estimates of plant and soiltype biomass (e.g. A and SA; table 1) and is easily implemented in a spreadsheet.…”
Section: Methodsmentioning
confidence: 99%
“…The growth of each soil type is a function of the abundance and the growth of the plant that cultivates it. Finally, each plant grows at a rate that is specific to each soil type [18].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our competition modelling focusing on per capita effects also confirmed this result, showing the strongest self-limitation in B. gracilis inoculated with its own, live, rhizospheric microbes. Prior work correlating the strength of PSF with species relative abundance [12,13] as well as pairwise studies examining PSF under competitor present/absent scenarios [16][17][18]46] set the stage for PSF as a potential driver of plant community dynamics, but do not wholly demonstrate it as a stabilizing mechanism that increases self-limitation. In addition, while negative conspecific density-or distance-dependent effects on seedling survival found in Janzen-Connell studies may result in negative frequency dependence when considered intergenerationally, we found that soil communities are able to intensify intraspecific interactions within the same generation.…”
Section: (A) Plant -Soil Feedbacks Increased Self-limitation In Boutementioning
confidence: 99%